One Acre Fund : outgrowing the board - Donnelly, Anne Cohn, (SAGE Knowledge. Cases., 2017)
One Acre Fund, a young, international, nonprofit social enterprisegoverned by friends of the founderhad grown rapidly since its inception. It now faces increasing demands for resources and key connections to major potential donors, expertise in going to scale, and managing expansion. The case presents this issue, which is commonly faced by new nonprofits, and how the organization, led by the board chair, seeks to resolve it through redesign of the board and major changes in board membership.